Material Pacification: How a Conflict Over Paving Uganda’s Tourism Road Got Accidentally Resolved - Christine, Ampumuza; Martijn, Duineveld; René, van der Duim (Tourism Planning & Development, 2023)
Starting from an Actor-network Theory (ANT) inspired relational perspective on object formation and material agency, this article analyses the controversies about plans to pave the Ruhija road through Bwindi Impenetrable National Park (Uganda). Based on interviews, ethnographic observations, and analysis of relevant documents, we examine the multiple ways in which the Ruhija road is enacted and objectified in conservation, tourism, and planning practices. We further show how these different objectifications of the Ruhija road not only led to enduring conflicts but also contributed to postponing the plans to pave the road. We argue that improving traction of the road pacified the conflicts. The partial solidification of the muddiest parts of the road unintentionally matched with the different “road realities” of the actors involved. Our analysis shows how the vibrancy of materiality is always relational, and can only be understood by taking into account the context of their objectification